Learning from pandemics: Applying resilience thinking to identify priorities for planning urban settlements - Shruti Syal (Journal of Urban Management, 2021)
Based in an interdisciplinary review of the literature on COVID-19 and recent outbreaks, this paper uses pandemics as a lens to examine the socio-ecological resilience of human settlements. This narrative literature review applies the conceptual framework for resilience developed for complex systems to identify five planning and policy issues critical to disease emergence, transmission, and outbreak. First, since urban settlements and activities facilitate pathogen transmission between species, reducing 'shocks' like zoonotic diseases and climate change requires not just prioritizing urbanization patterns and land use in urban policies for environmental health, but also animal rearing practices and biodiversity maintenance. Second, since disease transmission is linked to not just contact rate but also host susceptibility, reducing vulnerability by improving equity in access to essential infrastructures like housing, water, sanitation, healthy food, green/public spaces, healthcare-that impact human health directly and indirectly-is critical. In its absence, curbing disease transmission requires focusing on contact rate suppression, but doing so brings human activity to a halt, decimating the economy and livelihoods. Third, the persistence of many pathogens or their vectors in environmental media suggests that built environment & public health professionals must address maintenance of environmental quality at various scales. Fourth, there is a need for redundancy, be it in commodity supply chains (like PPE, food) or data management for say, monitoring & enforcement of home quarantines during a pandemic. Fifth, while it is crucial to have a centralized response for healthcare, decentralized infrastructure management has been critical during this outbreak: including participatory governance structures to recruit civil society in data collection and self-reporting, reliance on and quick development of mutual aid groups to distribute food and other essential supplies, localized approaches to repurposing infrastructures to create safe public spaces. This application of resilience thinking also evokes the need to study cities as social-ecological systems
Keywords: 710; Cities; Disease; Resilience; Social-ecological systems; Pandemics